2015
DOI: 10.3390/md13074179
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Characterization of FAU Gene/Protein from Marine Sponge Suberites domuncula

Abstract: Finkel-Biskis-Reilly murine sarcoma virus (FBR-MuSV) ubiquitously expressed (FAU) gene is down-regulated in human prostate, breast and ovarian cancers. Moreover, its dysregulation is associated with poor prognosis in breast cancer. Sponges (Porifera) are animals without tissues which branched off first from the common ancestor of all metazoans. A large majority of genes implicated in human cancers have their homologues in the sponge genome. Our study suggests that FAU gene from the sponge Suberites domuncula r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“… 92 , 93 Notably, it has recently been shown that even very simple animals, such as sponges and sea anemones, have homologs of many human disease genes. 94 , 95 C. intestinalis has only recently emerged as a model system. However, it has already been used to study certain human disease pathways, such as Huntington’s Disease 96 , 97 and Alzheimer’s disease (AD).…”
Section: Discussionmentioning
confidence: 99%
“… 92 , 93 Notably, it has recently been shown that even very simple animals, such as sponges and sea anemones, have homologs of many human disease genes. 94 , 95 C. intestinalis has only recently emerged as a model system. However, it has already been used to study certain human disease pathways, such as Huntington’s Disease 96 , 97 and Alzheimer’s disease (AD).…”
Section: Discussionmentioning
confidence: 99%
“…A study of the FAU protein from the marine sponge S. domuncula showed that sponge FAU protein displays a pro-apoptotic activity, as it increases apoptosis in human HEK293T cells (human embryonic kidney cells) as well as its human homolog and was shown to be more similar to its human homolog than to the one from Caenorhabditis elegans or Drosophila melanogaster . These findings implicate that the common metazoan ancestor probably possessed the FAU protein that was structurally and functionally similar to its recent version and has changed very little during evolution [ 57 ]. Additionally, the number, phases, and position of its introns were not significantly changed from sponges to humans.…”
Section: Players In Cellular Senescence and Apoptosismentioning
confidence: 99%
“…RPs have shown to be important tools for studying intron evolution, since the analysis of RPG introns in sponges revealed the same rate of conservancy between two different sponge species compared to the conservancy between sponges and humans [ 59 , 60 ]. Since S30 ribosomal protein is produced from the fusion protein transcribed from the pro-apoptotic regulatory gene FAU, its extraribosomal function may be connected to the regulation of apoptosis [ 57 ].…”
Section: Players In Cellular Senescence and Apoptosismentioning
confidence: 99%
“…However, it is not clear whether these substances are produced to protect the organism from potential carcinogens, or for a completely different ecological or physiological purpose. Most genes and pathways implicated in human genetic diseases and in neoplasia development and progression are highly conserved throughout evolution and can be found in early-branching metazoans such as non-bilaterians or even unicellular eukaryotes [19,28,[130][131][132][133][134][135][136][137][138][139]. This is probably due to the fact that most human diseases developed by abusing or distorting basic cellular processes common to all living beings.…”
Section: Metastasis-suppressor Genes Have Diverse Evolutionary Historiesmentioning
confidence: 99%